Determining the Impact of Economic Factors to the Gross Domestic Product in Bangladesh - Hasan, Mostofa Mahmud; Hossain, B.M. Sajjad; Sayem, Md. Abu (International Journal of Economics and Financial Issues, 2022)
Gross Domestic Product (GDP) is believed to be an indicator of a country’s economic condition. Bangladesh’s GDP increased at a pace of 8.15% in fiscal 2018-19 as per the base year 2005-06. By the year 2019, Bangladesh has become the seventh fastest-growing economy in the world. This paper used multiple regression analysis model for the macroeconomic factors. The aim of this study is to measure the effects of macroeconomic factors considering GDP as the dependent variables and inflation rate, import, and export are considered as independent. This paper represents that import and export are positively associated factors with GDP whereas inflation rate is a negatively associated factor. This study concluded with revealing the importance of conducting further study by considering more economic variables to measure the economic growth as a whole.